The basic concepts of the Baltic States image in the Russian periodical press after the collapse of the Soviet Union (1991–2009) - Denisenko, Viktor (Žurnalistikos tyrimai, 2015)
The Russian Federation and the Baltic States region are neighbors belonging to different geopolitical paradigms. Since 2004, Lithuania, Latvia and Estonia are members of the European Union and NATO. Russia after a short period of pseudo-democratization after the collapse of the Soviet Union came back to imperial discourse in so-called Putin’s era. The new imperial discourse is based on concepts of the “Russian world”, “compatriots” as well as on the specific strategy in relations with states from “near abroad”. Periodical press and another media (especially, TV) are involved in political processes of the Russian Federation. Research of the Baltic States’ image in the Russian periodical press shows how this particular geopolitical region (of the Baltic States) is represented in the Russian media in different periods after the collapse of the Soviet Union.